Synthesizing Digital Transformation and Knowledge Management to Drive SME Organization - Amalia, Mei Rani; Anggraeni, Ade Irma; Purnomo, Ratno (Eastasouth Institute, 2025)
This study explores the synthesis of knowledge management (KM) and digital transformation (DT) as performance and sustainability drivers in small and medium-sized enterprises (SMEs). Systematically review 37 Scopus-indexed articles, the study finds significant topics, methods, and concerns in utilizing KM and DT to drive organizational resilience, innovation, and flexibility. The study discovers that KM activities like knowledge sharing and digital capability development are critical enablers of DT initiatives, ensuring operational efficiency and innovation. Similarly, DT boosts KM through the enabling of technological platforms for the transfer and use of knowledge. The study also discovers challenges such as resource constraints, skill deficiencies, and resistance to change and provides practical recommendations to mitigate these challenges. Practical recommendations point to strategic alignment, policy support, and sustainability-driven strategies in advancing SME growth in uncertain environments. This incorporation enriches literature by formulating an all-encompassing KM and DT synergy concept, guiding stakeholders on how to create effective strategies for organizational development.